Narcotics interdiction at sea : the 1995 Council of Europe Agreement. - GILMORE, William C. (1992)
Highlights connection between the 1995 Council of Europe Agreement and the 1988 UN Convention Against Illicit Traffic in Narcotic Drugs and Psychotropic Substances, and the nature and extent of the efforts made in the former to supplement and strenghten the latter. Notes that particular attention is paid to developments relating to action against stateless vessels, measures taken at the request of the Flag State, and the central role accorded to the concept of preferential jurisdiction in instances where law enforcement activities are intiated by one party with the prior consent of the Flag State. Other issues addressed range from the regulation of the use of force to the payment of compensation.